The Moderating Role of Independent Commissioners on the Effect of Family Ownership on Social Disclosures - Elsandi, Rhismaya Okky; Supatmi, Supatmi (The Indonesian Journal of Accounting Research, 2024)
This study aims to empirically test the effect of family ownership on social disclosures with independent commissioners as a moderating variable. Our research sample is 98 Indonesian financial firms listed on the Indonesian Stock Exchange (IDX) in 2018-2021, resulting in 389 firm-year observations. We measure social disclosures using the weighted scores of 52 indicators of the 2018 Global Reporting Initiative (GRI), which can be broken down into four aspects: labor practices and decent work, human rights, society, and product responsibility. Family ownership is divided into direct and indirect family ownership. This study tests the research hypotheses using panel-data regression analysis. Our results reveal that firms with higher total and direct family ownership engage in lower social disclosures. On the other hand, indirect family ownership positively affects social disclosures. Independent commissioners motivate financial firms to engage more in social disclosures and moderate the impact of family ownership on social disclosures. Specifically, they make the effect of family ownership on social disclosures positive. Firms with a greater proportion of independent commissioners exhibit a stronger effect of family ownership on social disclosures. Based on the social disclosure aspects, family-owned firms tend to avoid social disclosures related to human rights, and independent commissioners motivate family firms to disclose more, especially those related to labor practices and decent work. Overall, our findings support the type II agency theory, arguing that family owners as majority shareholders increase agency conflicts by reducing social disclosure activities.